2018
DOI: 10.1016/j.rmcr.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Development of mediastinal adenitis six weeks after endobronchial ultrasound-guided transbronchial needle aspiration

Abstract: A 60-year-old man visited our hospital for further examination of an abnormal chest radiograph. Computed tomography (CT) images revealed enlarged mediastinal lymph nodes and multiple pulmonary nodules.Further evaluation by endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) was performed and he was diagnosed with sarcoidosis. Six weeks after EBUS-TBNA, he presented to the emergency department with a high-grade fever. CT scan revealed an enlarged mediastinal lymph node. He was diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In this study, oropharyngeal commensal bacteria were found in 39.2% of patients in the chlorhexidine mouthrinse group and in 49.1% of patients in the usual care group, and the genus Streptococcus was the most abundant in both groups. Oropharyngeal commensal bacteria such as the genera Streptococcus , Actinomyces , Gemella , and Prevotella were frequently reported as pathogens, and genus Streptococcus was identified as the pathogen in 14 of 29 cases of mediastinal infectious complications after EBUS-TBNA [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, oropharyngeal commensal bacteria were found in 39.2% of patients in the chlorhexidine mouthrinse group and in 49.1% of patients in the usual care group, and the genus Streptococcus was the most abundant in both groups. Oropharyngeal commensal bacteria such as the genera Streptococcus , Actinomyces , Gemella , and Prevotella were frequently reported as pathogens, and genus Streptococcus was identified as the pathogen in 14 of 29 cases of mediastinal infectious complications after EBUS-TBNA [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite concerns about serious infectious complications associated with EBUS-TBNA, there are no established strategies to prevent such complications following this procedure. We hypothesized that oral hygiene care is important in preventing infectious complications during the procedure because previous studies have suggested that oropharyngeal commensal bacteria can contaminate the working channel of an EBUS bronchoscope and thus can be inoculated into the target lesion by a contaminated aspiration needle [ 13 , 14 ]. Moreover, a recent retrospective study suggested that endobronchial intubation may prevent contamination by oropharyngeal commensal bacteria during EBUS-TBNA [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…EBUS-transbronchial needle biopsy (TBNAB) can be easily performed with sedation and jet ventilation [ 11 ]. EBUS-TBNA has very few complications related to any endoscopy such as: mild adenitis, pneumothorax and mild hemoptysis [ 12 ]. We present four cases where medical history correlates with undiagnosed mediastinum lymphadenopathy.…”
mentioning
confidence: 99%